Catalytic Gas‐Phase Cyclization of Glycolate Esters: A Novel Route Toward Glycolide‐Based Bioplastics. Issue 24 (26th November 2018) - De Clercq, Rik; Makshina, Ekaterina; Sels, Bert F.; Dusselier, Michiel
Abstract: A catalytic process to produce glycolide, the cyclic dimer of glycolic acid (GA), is proposed. Glycolide is the key building block of the biodegradable plastic polyglycolic acid. Instead of the current industrial two‐step route, which involves the polycondensation of GA and a subsequent backbiting reaction, a new route based on the gas‐phase transesterification of methyl glycolate (MGA) over a fixed catalyst bed is presented. With specific supported TiO2 catalysts, a high glycolide selectivity of 75–78 % can be achieved at the thermodynamically‐limited equilibrium conversion of MGA (54 % at 300 °C, 5.6 vol% MGA, 1 atm). The absence of solvent and the continuous nature of the process should allow for easy product separation and recycling of unconverted esters, while the few side‐products, i. e. linear alkyl glycolate dimers and trimers seem recoverable via methanolysis. The reaction is compared to the cyclization of other α‐hydroxy esters, such as methyl lactate to lactide, over the same catalysts, in terms of kinetics and thermodynamics. The absence of a methyl substitution on the α‐carbon seems to lead to faster cyclization kinetics of MGA when compared to methyl lactate or the double‐substituted methyl‐2‐hydroxy‐isobutyrate. Contrarily, glycolide production is less favored thermodynamically compared to lactide. The absence of glycolide decomposition at temperatures up to 300 °C however allows to increase equilibrium conversion by taking the endergonic reaction to higher temperatures. Abstract : Green plastics ! A novel process to produce glycolide, the cyclic dimer of glycolic acid, is proposed, via gas‐phase transesterification of methyl glycolate. Glycolide is the key building block of the biodegradable plastic polyglycolic acid.